THE DEVELOPMENT OF MYSTICAL THINKING IN CENTRAL ASIA, ITS SCIENTIFIC-PHILOSOPHICAL ESSENCE. - Shahnoza Tuychievna Tursunkulova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the article, opinions are given about the emergence of the history of Sufism in Central Asia during the Middle Ages, its scientific-philosophical essence, and historical significance. Sufism sects, their content, main problems are studied.